Connectivity-based identification of a potential neurosurgical target for mood disorders. (June 2020) - Sweet, Jennifer A.; Thyagaraj, Suraj; Chen, Zhengyi; Tatsuoka, Curtis; Staudt, Michael D.; Calabrese, Joseph R.; Miller, Jonathan P.; Gao, Keming; McIntyre, Cameron C.
Abstract: Objective: Stereotactic ablation (cingulotomy) and subcallosal cingulate deep brain stimulation (SCC DBS) of different regions of the cingulum bundle (CB) have been successfully used to treat psychiatric disorders, such as depression and bipolar disorder. They are hypothesized to work by disrupting white matter pathways involved in the clinical manifestation of these disorders. This study aims to compare the connectivity of different CB subregions using tractography to evaluate stereotactic targets for the treatment of mood disorders. Methods: Fourteen healthy volunteers underwent 3T-MR imaging followed by connectivity analysis using probabilistic tractography. Twenty-one anatomic regions of interest were defined for each subject: 10 CB subregions (including the classical cingulotomy and SCC DBS targets) and 11 cortical/subcortical structures implicated in mood disorders. Connectivity results were compared using Friedman and Bonferroni-corrected post-hoc Wilcoxon tests. Results: CB connectivity showed a high degree of regional specificity. Both of the traditional stereotactic targets had widespread connectivity with discrete topology. The cingulotomy target connected primarily to the dorsomedial frontal, dorsal anterior cingulate, and posterior cingulate cortices, whereas the SCC DBS target connected mostly to the subgenual anterior cingulate and medial/central orbitofrontal cortices. However, a region of the rostral dorsal CB, lying between these surgical targets, encompassed statistically equivalent connections to all five cortical regions. Conclusions: The CB is associated with brain structures involved in affective disorders, and the rostral dorsal CB demonstrates connectivity that is comparable to the combined connectivity of cingulotomy and SCC DBS neurosurgical interventions. The rostral dorsal CB represents a surgical target worthy of clinical exploration for mood disorders.